Impacto emocional por perdida de un familiar en un adolescente de 16 años de edad - Contreras Solorzano, Joselin Adriana (2020)
The loss of a family member is a very complex situation that all individuals must face at some point in life. When a loss occurs it occurs in an emotional impact on the person generating emotions of sadness, anger, anger, loneliness, abandonment due to the grieving process they are going through, if these symptoms continue or intensify they can generate depressive problems or even anxiety. On the other hand, it can be mentioned that the attachment that exists between individuals also has to do with the impact that it produces at the time of loss, which is why the attachment theory is revealed and in turn the types of attachments that exist. The current study is about the emotional impact of the loss of a family member in an adolescent whose objective is to identify the emotional impact that the death of a loved one can cause. In the research process for the collection of information, various techniques are used and also the use of tools that are essential to obtain a specific result based on the research topic. By means of all the information collected and the applied techniques, a diagnosis is obtained that will serve to proceed to carry out the psychotherapeutic plan based on the results obtained.